OP0111 Tocilizumab discontinuation after attaining remission in patients with rheumatoid arthritis who were treated with tocilizumab alone or in combination with methotrexate: results from a prospective, randomised, controlled study (THE SECOND YEAR OF THE SURPRISE STUDY). (12th June 2018) - Kaneko, Y.; Kato, M.; Tanaka, Y.; Inoo, M.; Kobayashi-Haraoka, H.; Amano, K.; Miyata, M.; Murakawa, Y.; Yasuoka, H.; Hirata, S.; Tanaka, E.; Miyasaka, N.; et al.
Abstract : Background: Feasibility of discontinuation of biologic agents in patients with rheumatoid arthritis (RA) who have reached stable remission has been investigated. Although evidence has been accumulating regarding tumour necrosis factor inhibitors, the possibility of tocilizumab-free strategy is still unclear. Objectives: To evaluate the sustained remission and low disease activity after discontinuation of tocilizumab in patients with RA who were treated with tocilizumab alone or in combination with methotrexate. Methods: The SURPRISE study was a 2 year randomised, controlled study. Patients with active RA despite methotrexate were randomised to tocilizumab added to methotrexate (ADD-ON) or switch to tocilizumab alone (SWITCH). At week 52, tocilizumab was discontinued in patients who achieved remission based on disease activity score for 28 joints (DAS28-ESR<2.6). The endpoints of the second year included tocilizumab-free sustained remission rates at week 104, sustained low disease activity rates, radiological outcomes assessed with the modified total Sharp score (mTSS), and safety. The efficacy of re-instituted tocilizumab/methotrexate was also assessed. Results: 105 patients who achieved remission at 52 week discontinued tocilizumab; 51 in the ADD-ON continued methotrexate and 54 in the SWITCH were observed without medication. Whereas sustained DAS28 remission rates at week 104 were 24% for the ADD-ON and 14% for the SWITCH (p=0.29), sustained low disease activity rate was significantly higher in the ADD-ON than in the SWITCH (55% vs 27%, p=0.005, figure 1). Radiographical progression was comparable in the 2 groups (mTSS; 0.37 vs 0.64, p=0.36). Re-start of tocilizumab induced remission in all patients except two irrespective of concurrent methotrexate after 36 weeks while re-start of methotrexate was effective only in a half of patients. Conclusions: Sustained low disease activity after tocilizumab discontinuation could be maintained with continued methotrexate in more than half of patients. Re-treatment with tocilizumab led remission in more than 90% patients. Disclosure of Interest: Y. Kaneko Grant/research support from: Abbvie, Eisai, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Jansen, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, UCB, M. Kato Grant/research support from: GlaxoSmithKline K.K., Actelion Pharmaceuticals, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Bristol-Myers, Chugai, Astellas, Abbvie, MSD, Daiichi-Sankyo, Pfizer, Kyowa-Kirin, Eisai, Ono, Speakers bureau: Daiichi-Sankyo, Astellas, Pfizer, Mitsubishi-Tanabe, Bristol-Myers, Chugai, YL Biologics, Eli Lilly, Sanofi, Janssen, UCB, M. Inoo: None declared, H. Kobayashi-Haraoka Speakers bureau: Chugai, Astellas, Bristol Myers Squibb, K. Amano Grant/research support from: Chugai Pharmaceutical Co.Ltd., Speakers bureau: Pfizer Japan, Tanabe-Mitsubishi, M. Miyata Employee of: Japanese Red Cross Society, Y. Murakawa Grant/research support from: Chugai, Ono, Daiichi, Teijin, Eisai, Nippon Kayaku, Tanabe-Mitsubishi, Paid instructor for: Kissei, Janssen, Eisai, Speakers bureau: Ono. Tanabe-Mitsubishi, Astellas, Chugai, UCB, Abbvie, Ayumi, Daiichi-Sankyo, Janssesn, Takeda, Sanofi, Teijin, Eli- Lilly, Teijin, H. Yasuoka Grant/research support from: Bristol Myers Squibb, Takeda, Japan Blood Products Organisation, Eizai, Daiichi-Sankyo, Novartis, Speakers bureau: Chugai, Actelion, Bristol Myers Squibb, S. Hirata Grant/research support from: Eli Lilly, UCB, Consultant for: Bristol-Myers Squibb, UCB, Paid instructor for: AbbVie, Eisai, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Jansen, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, UCB, E. Tanaka Speakers bureau: Abbvie, Ayumi Pharmaceutical, Bristol Myers Squibb, Chugai Pharmaceutical, Eisai Pharmaceutical, Nippon Kayaku, Pfizer, Takeda Pharmaceutical, UCB Pharma, N. Miyasaka: None declared, H. Yamanaka Grant/research support from: MSD, Astellas, AbbVie, BMS, Kaken, UCB, Ono, Ayumi, Eisai, Daiichi-Sankyo, Takeda, Tanabe-Mitsubishi, Chugai, Teijin, Torii, Nipponshinyaku, Pfizer, Consultant for: Pfizer, YL biologics, Takeda, Teijin, BMS, Nipponkayaku, Chugai, Tanabe-Mitsubishi, Daiichi-Sankyo, Astellas, Paid instructor for: Pfizer, YL biologics, Takeda, Teijin, BMS, Nipponkayaku, Chugai, Tanabe-Mitsubishi, Daiichi-Sankyo, Astellas, K. Yamamoto Grant/research support from: Astellas Pharmaceutical, Chugai Pharmaceutical, Eizai Pharmaceutical, Immunofuture Inc, Mitsubishi Tanabe Pharma Corporation, Santen Pharmaceutical, Pfizer Japan Inc., Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical, Mitsubishi Tanabe, Pfizer Japan, Astellas Pharma Inc, Diaichi Sankyo, Eli Lilly, Sanofi, Janssen, UCB, T. Takeuchi Grant/research support from: Astellas Pharma Inc, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc